2019
DOI: 10.1002/chem.201901374
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Concentration and Enantiomeric Composition of Amino Acids in Aqueous Solution by Using a Tetrabromobinaphthyl Dialdehyde Probe

Abstract: 3,3'-Diformyl-1,1'-bi-2-naphthol or its methoxymethyl-protected derivative is found to undergo ah ighly selective reactionw ith excess bromine in CH 2 Cl 2 at reflux to give the novel 5,5',6,6'-tetrabrominatedp roduct (S)-or (R)-2. The observed electrophilics ubstitution at the 5,5'-positons of an optically active binaphthyl compound is unprecedented. Unlike unbrominated 3,3'-diformyl-1,1'-bi-2-naphthol, which is not suitable for fluorescent recognition in water, compound (S)-2,i nc ombination with Zn 2 + ,e x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…These dynamic amine exchange reactions have been used to afford an attractive way to develop enantioselective fluorescent recognition systems for chiral amines. In addition to these dynamic amine exchange reaction-based chiral recognition systems, other enantioselective fluorescent recognition systems have also been established by using chiral 1,1′-bi-2-naphthol-3-al or its derivatives to react with enantiomeric amines to create imines that enantioselectively coordinate with introduced Zn 2+ ions, resulting in enantiomeric discrimination in the fluorescence response. Similar to reported dynamic amine exchange reaction-based fluorescent chiral recognition systems, the difference in the fluorescence response of these three-component systems likely originates from different coordination stability constants of Zn 2+ –chiral imine complexes, or different modes of coordination between the Zn 2+ / d -configuration of imine and the Zn 2+ / l -configuration of imine, yet it is not easy to clarify the enantioselective fluorescence response mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dynamic amine exchange reactions have been used to afford an attractive way to develop enantioselective fluorescent recognition systems for chiral amines. In addition to these dynamic amine exchange reaction-based chiral recognition systems, other enantioselective fluorescent recognition systems have also been established by using chiral 1,1′-bi-2-naphthol-3-al or its derivatives to react with enantiomeric amines to create imines that enantioselectively coordinate with introduced Zn 2+ ions, resulting in enantiomeric discrimination in the fluorescence response. Similar to reported dynamic amine exchange reaction-based fluorescent chiral recognition systems, the difference in the fluorescence response of these three-component systems likely originates from different coordination stability constants of Zn 2+ –chiral imine complexes, or different modes of coordination between the Zn 2+ / d -configuration of imine and the Zn 2+ / l -configuration of imine, yet it is not easy to clarify the enantioselective fluorescence response mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…(i) Integrating fluorescent BNDA into imines enables very low or even nonfluorescent backgrounds for facilely probing the processes of dynamic amine exchange reactions by measurement of the fluorescent response because the released BNDA can function as a fluorescent reporter for dynamic amine exchange reactions, which is favorable for establishing chiral fluorescent sensing systems. (ii) The axially chiral structure of used BNDA can confer chiral steric selectivity to amine exchange reactions compared to chiral imines composed of achiral amine and chiral aldehyde . (iii) Using SA or its derivatives to construct chiral imines is believed to impart a desirable pathway for facilitating dynamic behavior because of the formation of intramolecular hydrogen bonds that substantially decrease the electronic density of imine −CHN– bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Iqbal et al found that the 5,5',6,6'-tetrabromo-substituted compound (S)-16 can be dissolved in predominately water solution. [24] Thea queous solution of (S)-16 (1.0 10 À5 m, HEPES buffer/1 %D MSO,p H7.4) in combination with Zn(OAc) 2 (1.0 equiv) showed highly enantioselective fluorescent responses toward various amino acids.T he following ef values [(I L ÀI 0 )/(I D ÀI 0 )] were observed:4 4.5 at l max = 512 nm for valine;2 4.3 at l max = 575 nm for leucine;4 5.5 at l max = 574 nm for phenylalanine;3 0.3 at l max = 503 nm for glutamic acid;4 7.0 at l max = 504 nm for methionine;3 8.6 at l max = 496 nm for threonine;a nd 31.5 at l max = 575 nm for tyrosine.T hese enantioselectivities are generally higher than those of (R)-9 and (S)-14.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Iqbal et al. found that the 5,5′,6,6′‐tetrabromo‐substituted compound ( S )‐ 16 can be dissolved in predominately water solution [24] …”
Section: 1′‐binaphthyl‐based Probesmentioning
confidence: 99%